IMPROVING THE UTILIZATION OF TELLERS USING SIMULATION AT XYZ BANK - Nova Indah Saragih (Jurnal Ilmiah Teknologi Infomasi Terapan, 2018)
Simulation is one of the techniques of operationsresearch and management science that is most usedwidely. The goal of simulation is to estimate theperformance measures of the evaluated system usingcomputers. This paper provides the simulation oftellers to estimate and then improve its performancemeasure which is the utilization. The initial utilizationof XYZ Bank is 24.13% on average. Two scenario areconducted to improve the utilization. Scenario 1improves the utilization by 32.26% on average andscenario 2 improves the utilization by 47.84% onaverage. This paper suggests XYZ Bank to applyscenario 2 that can improve the utilization by 23.72%.